Application of a Lateral Pedicled Cranial Bone Flap for the Treatment of Secondary Zygomaticomaxillary Defects. Issue 7 (October 2019) - He, Wenpeng; Gong, Xi; He, Yang; Zheng, Lei; Zhang, Yi; Lai, Renfa
Abstract : Abstract: This study aimed to evaluate the effect of laterally-based pedicled cranial bone flap (LBPCBF) for the repair of secondary zygomaticomaxillary defects. Between December 2014 and December 2016, 6 patients with unilateral zygomaticomaxillary defects were selected; of these, 5 had trauma, and 1 was exposed to titanium mesh in the infraorbital area due to radiotherapy following total maxillectomy for right maxillary squamous cell carcinoma. Preoperatively, 3 patients suffered from an intraoral vestibular groove fistula, 2 suffered from an extraoral fistula, and 1 from local exposure of titanium mesh. Surgical treatment was implemented in all 6 patients, of which, the 5 trauma patients underwent debridement, reduction, and fixation of periorbital fracture, followed by repair of the defects in the infraorbital margin, anterior wall of maxillary sinus, and zygomatic body with LBPCBF, and then, reconstruction of the orbital floor with titanium mesh. The other patient with exposed titanium mesh underwent repair of defects in the infraorbital margin and anterior wall of the maxillary sinus with LBPCBF after titanium mesh trimming. Postoperative review at 6 months revealed disappearance of intraoral fistula, wound healing, and improvement of facial deformity in all 6 patients, of which 2 patients demonstrated postoperative ectropion. The application of LBPCBF can simultaneously repair bone defects in the infraorbital margin, anterior wall of maxillary sinus, and zygomatic body, as well as, supplement the soft tissue, thereby indicating a satisfactory treatment effect. Abstract : Supplemental Digital Content is available in the text